2006
DOI: 10.2147/nedt.2006.2.3.387
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of phantom bite syndrome with milnacipran ? a case series

Abstract: Phantom bite syndrome is characterized by an uncomfortable sensation mainly affecting corrected dentition in which no abnormality is clinically detectable. Despite repeated failures of dental surgery, sufferers persist in seeking bite correction from a succession of dentists. The etiology-pathogenesis of phantom bite is unknown but some consider the syndrome to be a psychosomatic disorder. Seven patients with this syndrome were treated with the serotonin and norepinephrine reuptake inhibitor milnacipran for 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 11 publications
0
32
0
1
Order By: Relevance
“…Previous reports describe cases in which amitriptyline [20][21][22][23][24], milnacipran [19] and duloxetine [25] were effective, but little is known about aripiprazole [21], and mirtazapine. We found that aripiprazole and mirtazapine may be as effective as amitriptyline for PBS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports describe cases in which amitriptyline [20][21][22][23][24], milnacipran [19] and duloxetine [25] were effective, but little is known about aripiprazole [21], and mirtazapine. We found that aripiprazole and mirtazapine may be as effective as amitriptyline for PBS.…”
Section: Discussionmentioning
confidence: 99%
“…Thorough clinical examinations were performed by at least three dentists, including prosthodontic and orthodontic specialists, to exclude occlusal discrepancies and temporomandibular joint disorders. Previously reported clinical characteristics and criteria were also considered for definitive diagnosis [12,26], Amitriptyline was prescribed as the first choice for psychopharmacological management based previous reports [19][20][21][22][23][24][25]. Other antidepressants or antipsychotic drugs were added or switched consensually according to weekly clinical assessments of symptom severity, quality of life, and adverse reactions.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,7,12 Phantom sensations may result owing to neuronal reorganization of adjacent regions of the thalamus into the deaf-ferented regions, which can lead the patient to report sensations of tooth awareness and pain. Thus, even after a change in or a loss of occlusal input, the central brain regions representing occlusal proprioception remain functional and unchanged.…”
Section: Explanation Of Phantom Bite Syndromementioning
confidence: 99%
“…7,9,13-18 Although the relationship among somatic preoccupation, chronic pain and occlusal disharmony rarely has been addressed, the results of a 2007 study showed that 35 (66 percent) of 53 patients with subjective occlusal-related problems also had a comorbid mental disorder. 9 …”
Section: Explanation Of Phantom Bite Syndromementioning
confidence: 99%